2018
DOI: 10.22456/1982-8918.81689
|View full text |Cite
|
Sign up to set email alerts
|

The Sport Education Model in Elementary and Secondary Education: A Systematic Review

Abstract: Este estudo consistiu em oferecer uma revisão atualizada das implementações mais recentes do Modelo de Sport Education (SEM) do primeiro ao 12º ano (6-18 anos), incluindo as mais novas tendências de pesquisa para estudos futuros. Uma revisão sistemática de 2013 a 2017 foi realizada utilizando os bancos de dados de maior referência e os artigos originais que incluíam informações sobre as implementações do SEM em qualquer grau escolar. A implementação do SEM expandiu-se enormemente nos últimos cinco anos para in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
0
17

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 19 publications
(27 reference statements)
6
33
0
17
Order By: Relevance
“…Regarding the hypotheses, it was proposed that said intervention (based on the SEM) would improve the participants' social competence (H1) and social acceptance among peers (H2). Finally, the impact of the intervention would not show differences, depending on gender (H3) in line with previous studies (Evangelio et al, 2018).…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…Regarding the hypotheses, it was proposed that said intervention (based on the SEM) would improve the participants' social competence (H1) and social acceptance among peers (H2). Finally, the impact of the intervention would not show differences, depending on gender (H3) in line with previous studies (Evangelio et al, 2018).…”
Section: Introductionsupporting
confidence: 90%
“…In the same line, some systematic reviews conclude that through interventions based on the SEM, there are improvements in technical-tactical skills (physical and cognitive physical domain), social and emotional development (Evangelio et al, 2018;González-Víllora et al, 2018) and motivational aspects (Chu and Zhang, 2018). In addition, meta-analysis (e.g., Sierra-Díaz et al, 2019) confirms benefits in motivation toward physical and sports activity, belonging and social responsibility, autonomy, and organization.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…[15]. Therefore, despite each model pursuing a main objective, a hybridization between both approaches may mutually complement each other's characteristics, and overcome some of their own limitations [14,16,17]. It has been evidenced that the hybridization of these two models allows for a broader and deeper scope of learning to be achieved than the development of these two pedagogical models separately [16].…”
Section: Se and Tgfu Models In Physical Educationmentioning
confidence: 99%
“…Previous research on SE has widely shown its instructional benefits and positive educational implications for students in the context of the school PE [18][19][20][21][22]. Regarding works that have examined the influence of SE on sportsmanship in students, Hastie and Sharpe [23] discovered that the use of a fair play accounting system could develop responsibility and positive social behaviors in elementary school students.…”
Section: Introductionmentioning
confidence: 99%